THE SECRET EXPLORERS AND THE PLANT POACHERS - King, SJ; O'Shea, Ellie (New York, New York : DK Publishing, 2021)
"Learn all about forest life, the amazing Venus flytrap, and the importance of conservation in the exciting eighth adventure with The Secret Explorers. This group of brilliant kids come together from all four corners of the globe to fix problems, solve mysteries and gather knowledge all over the planet -- and beyond. Whenever their help is needed, a special sign will appear on a door. They step through to the Exploration Station, and receive their mission... In this installment, Leah the biology expert and Gustavo the history buff are whisked away on a mission to a forest in North Carolina. There, they meet a botanist working to protect the amazing Venus flytrap -- an endangered species of plant -- from being stolen by poachers and sold for money. It'll take every bit of brainpower, bravery, and expertise that Leah and Gustavo have to stop the poachers and rescue the plants. Packed with fun illustrations and facts about plants, forest, wildlife, and the importance of conservation"
Includes quiz and answers.
Keywords: Rescues -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Scientists -- Juvenile fiction; Carnivorous plants -- Effect of poaching on -- Juvenile fiction; Poaching -- United States -- Prevention -- Juvenile fiction; Venus's flytrap -- Juvenile fiction; Poaching -- Prevention -- Juvenile fiction; Gifted children -- Juvenile fiction; North Carolina -- Juvenile fiction; Action and adventure fiction; Detective and mystery fiction